Photoactive perylenediimide metal–organic framework for boosting iodoperfluoroalkylation of alkenes and oxidative coupling of amines. Issue 1 (17th November 2021) - Liu, Zhengfen; Li, Chao; Chen, Jian; Li, Xiaobo; Luo, Fumang; Cheng, Feixiang; Liu, Jian-Jun
Abstract : A novel photoactive MOF was prepared based on an electron-deficient perylenediimide derivative, which exhibits excellent photocatalytic activities towards the iodoperfluoroalkylation of alkenes and the oxidation of amines to imines. Abstract : The incorporation of photoactive units into metal–organic frameworks (MOFs) is of particular interest due to their ability to endow the MOFs with additional properties such as photomagnetism, photomodulated electrical conductivity, and photocatalytic properties. Perylenediimides (PDIs), as a class of organic dye molecules with strong visible-light absorption ability and high photochemical activity, have attracted considerable interest because of their consecutive photoinduced electron transfer processes for the generation of energetic PDI radical anions. In this context, a novel photoactive MOF based on a perylenediimide derivative, Zn2 (diPyPI-Cl4 )(NDC)2 ·3DMF (MOF 1 ) (diPyPI-Cl4 = N, N ′-bis(pyridyl)-1, 6, 7, 12-tetrachloroperylene-3, 4, 9, 10-tetracarboxy bisimide, H2 NDC = 2, 6-naphthalenedicarboxylic acid), has been successfully constructed, which exhibits a porous three-dimensional framework with a pcu topology. MOF 1 that acts as an efficient and recyclable electron-transfer photocatalyst is applied for boosting the iodoperfluoroalkylation of alkenes and oxidation of amines to imines under mild conditions with high yields and excellent substrate application ranges. This photocatalyst has the advantages of high efficiency, low catalytic loading and easy availability, which is highly feasible from a synthetic point of view.